2002
DOI: 10.1359/jbmr.2002.17.8.1498
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Bone Loss in Ovariectomized Rats by Combined Treatment With Risedronate and 1α,25-Dihydroxyvitamin D3

Abstract: Bisphosphonates inhibit bone loss through inhibition of osteoclast-mediated bone resorption. At low doses, vitamin D metabolites can prevent bone loss in models of osteopenia in rats by an antiresorptive effect, while at high doses they also stimulate osteoblast activity and show an anabolic effect. Therefore, combined therapy with bisphosphonates and vitamin D analogs might be expected to be more effective than either treatment alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
46
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 51 publications
(98 reference statements)
3
46
1
1
Order By: Relevance
“…A couple of preclinical studies have reported on the efficacy of risedronate for trabecular bone loss using a rat model of postmenopausal osteoporosis: risedronate suppressed bone resorption and prevented trabecular bone loss in ovariectomized rats [5,14]. In the present study, the effect of risedronate on the trabecular and endocortical bone was considered to be suppression of both bone resorption (ES/BS) and bone formation (trabecular BFR/BV and endocortical BFR/BS) in terms of suppression of bone turnover.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A couple of preclinical studies have reported on the efficacy of risedronate for trabecular bone loss using a rat model of postmenopausal osteoporosis: risedronate suppressed bone resorption and prevented trabecular bone loss in ovariectomized rats [5,14]. In the present study, the effect of risedronate on the trabecular and endocortical bone was considered to be suppression of both bone resorption (ES/BS) and bone formation (trabecular BFR/BV and endocortical BFR/BS) in terms of suppression of bone turnover.…”
Section: Discussionmentioning
confidence: 84%
“…However, continuous treatment attenuated trabecular bone loss 6 weeks after OVX despite sufficiently suppressing bone turnover, probably because of the insufficient dosing of risedronate during the 6 weeks after OVX. In fact, high dose risedronate treatment in OVX rats is able to prevent trabecular bone loss [5,14]. Although the effect of continuous treatment on trabecular bone mass was diminished 6 weeks after OVX, two-way factorial ANOVA showed that pre-and post-OVX treatments had an additive effect on trabecular bone mass in both the short-and long-term experiments.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study (65) has suggested that calcitriol dose-dependently exhibited inhibitory effects on osteoblastic activity. Thus, although we are unable to rule out an effect of calcitriol in producing the ABD in our animal model, the dose and the actions of 1,25(OH)2D3 in previous studies (57,58,61) suggest that it may not have been the cause of the ABD we observed.…”
Section: Discussioncontrasting
confidence: 57%
“…The exact effects of calcitriol on bone are unclear. At low doses, vitamin D metabolites can prevent bone loss in models of osteopenia in rats by an antiresorptive effect, whereas at high doses they also stimulate osteoblast activity and show an anabolic effect (57). Bone histomorphometry in another in vivo study showed that 1,25(OH) 2 D 3 alone exerts a potent proliferative effect on the osteoblasts but depresses their mineralizing capacity in a dose and time dependent manner (58).…”
Section: Discussionmentioning
confidence: 99%
“…Several preclinical studies have demonstrated the efficacy of risedronate for preventing cancellous bone loss in rat models of osteopenia. Risedronate suppresses bone resorption and prevents cancellous bone loss in ovariectomized rats [8,31], while it prevents loss of cancellous bone mass, bone density and bone strength without affecting cortical bone parameters in sciatic neurectomy rats or hindlimb-immobilized rats [18,30]. The absence of any adverse effect of risedronate on longitudinal and radial bone growth has been confirmed [18].…”
Section: Discussionmentioning
confidence: 82%